Artificial Tanning Devices. - Organization, World Health (World Health Organization, 2017)
Skin cancer is the most common form of cancer among light-skinned populations. The chief environmental cause of skin cancer is ultraviolet radiation (UVR). UVR exposure comes mainly from the sun but over the past three decades there has been an increase in the use of artificial sources of UVR in the form of artificial tanning devices such as sunbeds stand up booths and facial tanners. This deliberate exposure to UVR for cosmetic purposes is increasing the incidence of the major types of skin cancer and driving down the age of first appearance.